Konsep Positivisme dalam Pembelajaran Bahasa Indonesia di Era Merdeka Belajar - Nelita Indah Islami; Sofyan Sauri (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
The background in this article is about the policies that have been offered by the Minister of Education and Culture Nadiem Makarim regarding the Independent Learning curriculum. This concept requires a response from educators to provide views on the program. The writing of this article aims to describe the concept of positivism philosophy towards Indonesian language learning in the Merdeka Learning era. The method used is a literature study with data collection carried out by literature searches from relevant research for later analysis. The result of this article is the concept of positivism in learning Indonesian in the Merdeka Learning Era from the aspects of ontology, epistemology, and axiology.